Investigating the effect of BT direction on W source-to-core pathways during the SAS-VW campaign on DIII-D - J.D. Mateja; S.A. Zamperini; T. Odstrcil; J.H. Nichols; T.E. Ray; A. Cacheris; T. Abrams; A.G. McLean; G. Sinclair; S.H. Messer; R. Maurizio; D.M. Thomas; et al. (Nuclear Materials and Energy)
Experiments using the V-shaped closed slot tungsten (W) coated SAS-VW divertor in DIII-D studied the effects of the BT direction on core contamination of eroded tungsten from a closed slot divertor configuration. Core W content is inferred using soft-X ray tomography (SXR) and vacuum ultraviolet spectroscopy (SPRED), while W divertor erosion is inferred from visible spectroscopy of W emission (400.9 nm) measured by in-slot filterscopes (filtered photo-multipliers). Post-mortem analysis from the campaign discovered tile misalignment leading to suspected pronounced leading-edge erosion in the unfavorable BT direction (ion B→×∇B→ drift away from divertor) likely not captured by diagnostics. However, empirical findings show up to ∼ 2-3x larger core contamination in the favorable BT direction even considering no additional W erosion from leading edges. A “source-to-core efficiency factor” is derived to estimate the effects of leading-edge erosion and compare W contamination for two pairs of H-mode discharges in opposite BT directions. While having differing absolute parameters, similar core impurity density gradients suggest comparable core impurity transport. These results show that favorable BT may have stronger source-to-core pathways for W impurities sourced from the outer divertor region. Possible explanations could include the effects of E→×B→ drifts on W transport in the scrape-off-layer (SOL) as well as previously determined fast SOL inner target directed flows in favorable BT.